Efficacy and safety of dapagliflozin in the treatment of chronic heart failure: A protocol for systematic review and meta-analysis. Issue 26 (2nd July 2021) - Dong, Xueyan; Ren, Lili; Liu, Yueli; Yin, Xuewei; Cui, Siyuan; Gao, Wulin; Yu, Liming
Abstract: Background: As the last link in the chain of cardiovascular events, chronic heart failure (CHF) has high morbidity, high mortality, and poor prognosis. It is one of the main causes of death and disability worldwide. As a new drug for the treatment of chronic cardiovascular disease, dapagliflozin, the efficacy, and safety issues are still the focus of attention. Therefore, we conducted a meta-analysis to evaluate the efficacy and safety of dapagliflozin in the treatment of CHF. Methods: According to the search strategy, regardless of publication date or language, randomized controlled trials (RCTs) of dapagliflozin for CHF will be retrieved from 8 databases. First of all, the literature was screened according to the eligibility criteria, and use the Cochrane Collaboration's tool to assess the quality of the included literature. Then, using Rev Man 5.3 and STATA 14.2 software for traditional meta-analysis. Finally, the evaluation of the quality of the evidence and the strength of the recommendations will adopt the Grading of Recommendations, Assessment, Development and Evaluation method. Results: This study will evaluate the efficacy and safety of dapagliflozin for CHF, thereby providing more evidence support for clinical decision-making in CHF. Conclusion: Our research will provide more references for the clinical medication of patients with CHF. Protocol registration number: INPLASY202150046